The Influence of Content Marketing in the Tiktok Application and Online Customer Reviews on Purchasing Decisions for Skincare Skintific (Case Study of Generation Z in Jambi City) - Salsabilah, Nafilah; Musnaini, Musnaini; Yuniarti, Yenny (East Asian Journal of Multidisciplinary Research, 2024)
This research aims to determine the influence of content marketing in the TikTok application and online customer review on purchasing decisions for Skintific skincare (case study of Generation Z in Jambi City). This research uses quantitative methods with data collection techniques by distributing likert scale questionnaires. The type of data used is primary data obtained from filling out questionnaires via google forms. The analytical method used is multiple linear analysis using SPSS version 26 software. The sample in this research was 100 consumers who had purchased Skintific skincare using a purposive sampling method. The results show that content marketing and online customer review have a positif and significant influence on purchasing decisions, both simultaneously and partially, and the variable that dominates the influence is online customer review.